Climate Change - Heather Hudak (United States Crabtree Publishing Co,US, 2019)
"Climate Change is a hot-button topic today and one that requires skill to examine and grasp different viewpoints. This book introduces readers to multiple perspectives on the topic and encourages them to objectively view local, national, and global connections to help them form knowledgeable points of view."--